Systematic Literature Review: Pengaruh Pola Makan Kariogenik pada Anak Sekolah Terhadap Status Kesehatan Gigi dan Mulut - Priandini, Aulia; Larasati, Ratih; Hadi, Sunomo; Prasetyowati, Silvia (Barongko: Jurnal Ilmu Kesehatan, 2024)
The maintenance of dental health in school-aged children is crucial as their dental condition will impact their oral health in adulthood. Consumption habits of cariogenic foods such as sugar can increase the risk of dental caries. Therefore, regulating dietary patterns to avoid excessive sugar consumption is important in reducing this risk. The aim of this study is to elucidate the cariogenic dietary patterns in school children concerning the status of dental and oral health through article reviews. The research strategy employed was a literature review obtained from academic databases including Google Scholar, ProQuest, and Science Direct, focusing on publications within the last 5 years. Keywords used were "Cariogenic food," "Cariogenic," "School Children," and "Oral Hygiene," searched using Boolean method, yielding 4 articles for analysis. Two journals were found addressing oral health maintenance behaviors, one focusing on brushing time, five discussing cariogenic snacking patterns, one examining dental visits, and two exploring dental caries and brushing frequency. The majority of journals utilized a cross-sectional study design, with one employing descriptive analytics study design. The sample sizes varied from 40 to 550 respondents.From the results of this research, it is concluded that the consumption pattern of cariogenic foods, such as biscuits and donuts, has a significant impact on the incidence of dental caries among elementary school children and junior high school students in various regions.